Systems biology in cancer research and drug discovery - Azmi, Asfar S. (Dordrecht : Springer, 2012)
''Systems Biology in Cancer Research and Drug Discovery'' provides a unique collection of chapters, by world-class researchers, describing the use of integrated systems biology and network modeling in the cancer field where traditional tools have failed to deliver expected promise. This book touches four applications/aspects of systems biology in understanding aberrant signaling in cancer; in identifying biomarkers and prognostic markers especially focused on angiogenesis pathways; in unwinding microRNAs complexity; and in anticancer drug discovery and in clinical trial design. This book revie
pt. 4. Network Modeling in Cancer Drug Discovery and Clinical Trials. Development and Clinical Implementation of Reverse Phase Protein Microarrays for Protein Network Activation Mapping: Personalized Cancer Therapy / Mariaelena Pierobon, Julie Wulfkuhle, Lance A. Liotta and Emanuel F. Petricoin III -- The Principle of Rational Design of Drug Combination and Personalized Therapy Based on Network Pharmacology / Jianghui Xiong, Simon Rayner, Fengji Liang and Yinghui Li -- Relevance of Network Hierarchy in Cancer Drug-Target Selection / Aritro Nath and Christina Chan -- Computational Infrastructures for Large-Scale Data Access and Analysis in Post-Genomic Clinical Trials / Manolis Tsiknakis -- Network Pharmacology: An Emerging Area in Anti-Cancer Drug Discovery / Asfar S. Azmi, Frances W. J. Beck, Bin Bao, Fazlul H. Sarkar and Ramzi M. Mohammad.
Includes bibliographical references and index.
Keywords: Cancer -- Research; Systems Biology; Drug development; Drugs -- Design; Pharmacy -- Technological innovations